Evaluasi Kinerja Ruas Jalan Di Kota Dumai Dengan Menggunakan Metode PKJI Tahun 2014 dan Aplikasi PTV Visum 22 - Wiwi Safitri (Politeknik Negeri Bengkalis, 2022)
Dumai City is the city with the second widest administrative area with a population growth rate of 2.17% in 2020. In the face of rapid population growth, the Dumai City government balances it by constructing public facilities, such as a city mall and a caring market. In the future, the Dumai City government plans to carry out the construction house of worship dumai Islamic center and the health services of the Awal Bross Dumai Hospital. With these buildings and facilities, of course, it will cause a large traffic generation and pull. traffic generation and pull if not balanced with additional road capacity will result in congestion.Based on the results of field reviews, 12 roads in Dumai City have the potential to experience congestion. Therefore, it is necessary to evaluate the performance of roads in Dumai City. Based on the results of the evaluation using the 2014 PKJI, the Jalan Jend Sudirman section has a degree of saturation value of 0.84, meaning that the Jalan Jend Sudirman section has experienced congestion at a certain time. Meanwhile, based on the results of modeling using the PTV Visum Application, Jalan Sudirman is the busiest road passed by vehicles with a total movement of 290 movements/day.